Assessment of livestock water productivity in Seno and Yatenga Provinces of Burkina Faso - Amole, Tunde A.; Adekeye, Adetayo; Ayantunde, Augustine A. (Frontiers Media, 2021)
The expected increase in livestock production to meet its increasing demand could lead to increased water depletion through feeds production. This study aimed at estimating the amount of water depletion through feeds and its corresponding productivity in livestock within the three dominant livestock management systems namely sedentary-intensive, sedentary-extensive, and transhumance in Yatenga and Seno provinces in the Sahelian zone of Burkina Faso. Using a participatory rapid appraisal and individual interview, beneficial animal products, and services were estimated, and consequently, livestock water productivity (LWP) as the ratio of livestock products and services to the amount of water depleted. Our results showed feed resources are mainly natural pasture and crop residues are common in all the management systems though the proportion of each feed type in the feed basket and seasonal preferences varied. Consequently, water depleted for feed production was similar across the systems in both provinces and ranged from 2,500 to 3,200 m−3 ha−1 yr−1. Values for milk (40 US$US$/household) and flock offtake (313 US$/household) derived from the transhumant system were higher (P < 0.05) than those from other systems in the Seno province. With higher returns from the beneficial outputs, LWP was higher (0.11 US$ m−3) in the transhumant system than other systems in Yatenga, but similar with sedentary-intensive in Seno Province Multiple regression analysis results showed that LWP had a significant positive relationship with flock offtake in Yatenga but milk and flock offtake in Seno. The study concluded that sedentary-intensive and transhumant system with more market-oriented beneficial outputs and much dependence on less-water-depleted feed resources will improve livestock water productivity in dry areas. Besides, interventions to improve livestock water productivity through beneficial outputs must recognize the unique socio-cultural context of the livestock farmers.